Gallery 6: The Life of Saint Teresa of Avila (Santiago Series) - Ojeda, Almerindo E. (PESSCA, 2014)
Adriaen Collaert (c.1560-1618) and Cornelis I Galle (1576-1650) designed a series of twenty four engravings on the life of Saint Teresa de Avila (see Gallery 5). This series served as the basis for two series of paintings on the life of the Saint currently in the Convento del Carmen San José (Carmen Alto) in Santiago, Chile. They are known as the Large Series and the Short Series on the Life of Saint Teresa (see Mebold 1987, 54-108). The Large Series on the Life of Saint Teresa consists of thirteen paintings, each measuring two meters in height by two and a half in width. The Small Series on the life of the Saint consists of twenty paintings, each measuring 1.22 meters of height by 1.63 meters of width. Both series were produced by an unknown member of the Cuzco School of painting. Apparently, he was a follower of José Espinoza de los Monteros, the author of the Cuzco series on the life of Saint Teresa featured in Gallery 5. The Large Series was produced around 1690 and the Small Series around 1694 (see Mebold 1987, loc. cit.). To visit this gallery, follow the navigation panel below throughout this website. To move through the gallery, click on the down-arrow; to retrace your steps, click on the up-arrow.
Keywords: Santa Teresa de Ávila; Collaert y Galle; http://purl.org/pe-repo/ocde/ford#6.03.00